Decreased sound tolerance in a Canadian University Context: Associations with autistic traits, social competence, and gender in an undergraduate sample - Silas Manning; Natalia Van Esch; Nichole E. Scheerer (PLoS ONE, 2025)
Disorders of decreased sound tolerance such as misophonia and hyperacusis cause significant distress through strong negative emotional and physiological reactions to everyday sounds. These conditions have been associated with poor mental and physical health as they impact day to day life. Prior to the recent development of consensus definitions of misophonia and hyperacusis, attempts to determine the prevalence of these conditions have been hindered by the ambiguity and inconsistency of their descriptions. Despite this, certain populations have been suggested to more frequently experience misophonia and hyperacusis, namely younger people and autistic people. Furthermore, there has been conflicting evidence regarding whether these conditions are more prevalent among women. Post-secondary campuses are often sensory-rich. As such, students with misophonia and hyperacusis are likely to experience distress. For this reason, we sought to investigate the prevalence of misophonia and hyperacusis in a Canadian university sample, and explore the relations between these conditions and gender, autistic traits, and overall social competence. As exposure to many everyday sounds can be highly aversive for individuals with misophonia and/or hyperacusis, these individuals often attempt to avoid environments in which distressing sounds are encountered. It is therefore possible that poorer social competence may be a secondary effect of these conditions. To investigate these relations, 2080 students completed an online survey using multiple established self-report measures of decreased sound tolerance. Clinical misophonia was detected in 12–18% of participants, and hyperacusis in 6–17%. Both conditions were significantly more prevalent among women than men. Both conditions were found to be weakly to moderately positively correlated with autistic traits, and weakly to moderately negatively correlated with social competence. These results highlight decreased sound tolerance as a significant issue at Canadian post-secondary institutions, calling for steps to be taken to mitigate its effects.